2006
DOI: 10.1007/s00414-006-0131-9
|View full text |Cite
|
Sign up to set email alerts
|

Successful RNA extraction from various human postmortem tissues

Abstract: Recently, several authors described the observation that RNA degradation does not correlate with the postmortem interval (PMI), but rather with other parameters like environmental impact and the circumstances of death. Therefore, the question arose if the analysis of gene expression could be a valuable tool in forensic genetics to contribute to the determination of the cause of death. In our study, six human tissues obtained from six individuals with PMI varying between 15 and 118 h were used for total RNA ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 23 publications
(28 reference statements)
4
67
0
5
Order By: Relevance
“…In opposition to this result, Heinrich et al, (2007) and Preece & Cairns, (2003) reported an absence of significant correlation between mRNA degradation and PMI in human brain tissue. Possible explanations for the inability to detect a clear relationship between reduced RNA quantity and the increased duration of PMI in human tissue studies include the confounding effects of greater intersubject variability and agonal or neuropathological variables on RNA degradation (Catts et al, 2005).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In opposition to this result, Heinrich et al, (2007) and Preece & Cairns, (2003) reported an absence of significant correlation between mRNA degradation and PMI in human brain tissue. Possible explanations for the inability to detect a clear relationship between reduced RNA quantity and the increased duration of PMI in human tissue studies include the confounding effects of greater intersubject variability and agonal or neuropathological variables on RNA degradation (Catts et al, 2005).…”
Section: Discussionmentioning
confidence: 68%
“…The brain was selected as a target tissue because it is well isolated and protected by the skull. In addition, several studies reported the generalized stability of brain mRNA transcripts (Johnson et al 1986;Cummings et al 2001;Inoue et al 2002;Miller et al 2004;Ervin et al 2007;Heinrich et al 2007 andLiu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although RNA is generally believed to be highly unstable and prone to degradation due to the action of ribonucleases and environmental factors such as pH, UV light, and moisture [1], recent advances in molecular forensics revealed a number of RNA markers successfully amplifiable under certain postmortem and/or in vitro conditions [2][3][4][5][6]. For instance, Karlsson et al [7] detected mRNA from the ÎČ-actin and GAPDH genes in 27-year-old blood stains; however, the study design did not ensure that polymerase chain reaction (PCR) amplification products truly originated from cDNA templates and not from contaminating genomic DNA.…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to the identification of body fluids and tissues using nucleic acid biomarkers (Courts and Madea, 2011;Haas et al, 2009;Juusola and Ballantyne, 2003;Zubakov et al, 2008;, the application of molecular pathological examination based on postmortem gene expression profiles to death processes appears to be still challenging. Despite technical advances in resolving the difficulties of sensitivity and standardization (Catts, 2005;Heinrich et al, 2007b;Lee et al, 2005), there remain limitations primarily due to the restricted understanding of molecular physiology at the time of death and, subsequently, the insufficiency of well-established forensic RNA biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…To test this idea, we primarily focus on brain tissues because neuronal cells abundantly express HSPs and are highly vulnerable to a variety of cellular stresses, such as hypoxia/anoxia as well as disturbances in energy homeostasis (Hecker and McGarvey, 2011;Stetler et al, 2010). Furthermore, brain tissues also have a practical advantage in postmortem RNA profiling; it has been demonstrated that postmortem gene transcripts in brain tissues are relatively stable and intact with longer PMI, and are thus suitable for extraction and quantitative analyses of RNA (Heinrich et al, 2007a;2007b;Leonard et al, 1993;Popova et al, 2008). Therefore, the present study aims to quantitatively analyze a subgroup of brain-enriched HSP mRNA transcripts particularly in the postmortem human occipital lobes, thus gaining useful clues on their differential profiles by the cause of death, such as traumatic injury (TI), mechanical asphyxiation (ASP), or sudden cardiac death (SCD).…”
Section: Introductionmentioning
confidence: 99%